2020
DOI: 10.1371/journal.pone.0226134
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden of adverse childhood experiences across 14 states

Abstract: Objective To examine whether the relationship between Adverse Childhood Experiences (ACEs) and health outcomes is similar across states and persists net of ACEs associations with smoking, heavy drinking, and obesity. Methods We use data from the Behavioral Risk Factor Surveillance System for 14 states. Logistic regressions yield estimates of the direct associations of ACEs exposure with health outcomes net of health risk factors, and indirect ACEs-health associations via health risk factors. Models were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 59 publications
1
64
0
3
Order By: Relevance
“…A growing body of research shows that ACEs can lead to changes in the structure and function of children's developing brains resulting in chronic dysregulation of the stress response as well as other hormones that regulate functions such as heart rate, blood pressure, metabolism, appetite, and reproduction [34][35][36][37], and long-term changes in the brain and immune system leading to increased measures of inflammation and impairments of certain immune functions [38,39]. Consistent with such physiological changes, studies of health outcomes have shown that ACEs can be plausibly linked to higher odds of asthma, arthritis, cardiovascular disease, COPD, and health risks such as obesity, smoking, and heavy drinking [e.g., 13,18,23]. This study provides the first US estimate of the economic burden of these negative health outcomes of ACEs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A growing body of research shows that ACEs can lead to changes in the structure and function of children's developing brains resulting in chronic dysregulation of the stress response as well as other hormones that regulate functions such as heart rate, blood pressure, metabolism, appetite, and reproduction [34][35][36][37], and long-term changes in the brain and immune system leading to increased measures of inflammation and impairments of certain immune functions [38,39]. Consistent with such physiological changes, studies of health outcomes have shown that ACEs can be plausibly linked to higher odds of asthma, arthritis, cardiovascular disease, COPD, and health risks such as obesity, smoking, and heavy drinking [e.g., 13,18,23]. This study provides the first US estimate of the economic burden of these negative health outcomes of ACEs.…”
Section: Discussionmentioning
confidence: 99%
“…We estimate healthcare costs of exposure to ACEs in California, by combining prevalence data from four years of the California Behavioral Risk Factor Survey (BRFS) with estimates of healthcare costs during 2013 from Dieleman et al [12] for those chronic conditions identified as plausibly linked to ACEs in Waehrer et al [13] The California BRFS is part of the Behavioral Risk Factor Surveillance System (BRFSS), the US system of cross-sectional state-based telephone surveys of residents' health-related behaviors. State health departments queried residents aged 18 and older in all 50 states and 3 US territories about demographics, risk behaviors, chronic health conditions, and use of preventive services using a standardized questionnaire developed in collaboration with the Centers for Disease Control (CDC).…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations